INCREASING THE DURABILITY OF LARGE-CALIBER GUN BARRELS BY STRENGTHENING THEM BY SURFACE PLASTIC DEFORMATION - AFTANAZIV, IVAN; SHEVCHUK, LILIA; TOPCHII, VLADYSLAV; STROHAN, ORYCA; STRUTYNSKA, LESYA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
A description of the technology and its implementing devices for strengthening the internal surface of the bore of artillery and tank guns by surface plastic deformation is given. It is recommended to carry out the strengthening treatment in two stages - to rivet the inner working surface of the barrel with hardened steel balls, and then to apply a heat-resistant hard alloy coating with hard alloy deformable bodies made of the VK6 alloy.It was established that as a result of this strengthening treatment, residual compressive stresses are formed in the near-surface layer of the borehole material, its surface microhardness increases, and the resistance of the metal of the working surface of the barrel to burnout and cracking increases. In total, this increases the resistance of the barrel material to its wear during cannon shots.The design of the strengthening device for this treatment was created. It consists of a cylindrical stiffener with deformable bodies, an electric drive motor and a torque transmission mechanism from the motor shaft to the stiffener. In the process of strengthening treatment, the device is moved along the channel of the gun barrel, the strengthener rolls over the processed inner surface of the barrel, and rivets its material. The provided strengthening thickness is 0.15-0.20 mm, the thickness of the applied hard alloy coating is up to a hundred microns.Proposed designs of stiffeners for two-stage strengthening treatment by the method of vibration-centrifugal strengthening of the bores of large-caliber artillery guns. The proposed strengthening spaces behind the structural drilling are energy-saving, and do not provide for the maintenance of highly qualified service personnel.
Keywords: gun; barrel; artillery; hard alloy; coating; wear; surface strengthening; thickness of strengthening